DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON MICROSOFT SWAY TO IMPROVE SPATIAL THINKING SKILLS - Ika Listiqowati; Iwan Alim Saputra; Rendra Zainal Maliki; Khairurraziq Khairurraziq; Arifuddin Abd Muis (Universitas Labuhanbatu, 2026)
Purpose - This study aims to develop an interactive learning media in Microsoft Sway to enhance participants' spatial thinking skills.Methodology - Method study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study population consisted of grade 11 students at SMA N 1 Banawa across 8 classes. A sample of 30 participants was drawn from class XI C IPS. The instrument included 1) tests to think spatially as a pre-test and post-test, 2) questionnaire validation and eligibility expert technology learning, and 3) questionnaire teacher and participant responses to educate. Analyse data for effectiveness testing using the N-Gain test. Eligibility was measured based on expert validator results, technology learning outcomes, teacher and participant responses, and the educational use percentage formula.Findings - Research results obtained results validation media expert with a score of 96.2 is included in the excellent category, or worthy, which is Very worthy, and did need to be revised; however, for perfection, the fixed validator product provides suggestions for improvement. From the effectiveness test, an N-gain value of 0.50, or an enter criterion of medium, was obtained, indicating that Microsoft Sway interactive media was developed effectively to improve spatial thinking.